Profiling sprints using on-body sensors - Taherian, S.; Pias, M.; Harle, R.; Coulouris, G.; Hay, S.; Cameron, J.; Lasenby, J.; Kuntze, G.; Bezodis, I.; Irwin, G.; Kerwin, D. (8th IEEE International Conference on Pervasive Computing and Communications Workshops (PERCOM), 2010, 2010)
This paper describes the design, implementation and deployment of a wireless sensor system for athletes. The system is designed to profile sprints based on input from on-body sensors that are wirelessly connected to a nearby infrastructure. We discuss the choice and use of inexpensive Force Sensitive Resistors (FSRs) to measure foot event timings and provide a detailed analysis of the profiling method used to represent high-level information to the coaches and athletes. In this profiling method, we detect sprinting intervals from high-resolution sensor data, and compute the ground contact times for sprinting performances. We validate our results using force plates and show that the system achieves comparable accuracy in measuring the foot contact times (millisecond accuracy) without the limitations of one or few steps.